2018
DOI: 10.1155/2018/5374725
|View full text |Cite
|
Sign up to set email alerts
|

The Age at Diagnosis of Autism Spectrum Disorder in Children in Japan

Abstract: Background No large-scale study of the timing of autism spectrum disorder (ASD) diagnosis has been performed in Japan to date. The aim of this study was to examine sex differences and annual trends in age at diagnosis of ASD using clinical data. Methods Clinical data for children aged less than 18 years diagnosed with ASD between January 1, 2009, and December 31, 2013, and in whom follow-up was possible 1 year after diagnosis, were extracted. Results The mean age at ASD diagnosis was 7.2 ± 4.2 years and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
2
26
2
Order By: Relevance
“…In contrast to results from Japan, which did not show a difference in age at diagnosis between genders [ 82 ], the distribution of age at diagnosis differed between boys and girls in our study, with significantly more girls than boys receiving early diagnosis, especially in year 5. At this point, the male-to-female ratio was at its lowest—3.46:1—remaining below 4:1 until year 9.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to results from Japan, which did not show a difference in age at diagnosis between genders [ 82 ], the distribution of age at diagnosis differed between boys and girls in our study, with significantly more girls than boys receiving early diagnosis, especially in year 5. At this point, the male-to-female ratio was at its lowest—3.46:1—remaining below 4:1 until year 9.…”
Section: Discussioncontrasting
confidence: 99%
“…From Spain, a study using a two-step screening and diagnosis procedure, reported a mean age at diagnosis of three years and 9 months in preschool children and seven years in children aged 10–12 years [ 61 ], while 80% of our cases had been diagnosed before the age of eight. Finally, seven years was the mean age at diagnosis reported in a study from Japan based on administrative data [ 82 ], with more diagnoses occurring at age three compared to our study. Different environmental expectations between Greece and Japan in the preschool setting with regard to the children’s behavioral and communication abilities, or different screening and early intervention service provision, might account for the pronounced disparity between the two countries.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Among the children with ASD, the proportion of boys was 75.4%. This is almost the same figure as that reported in a profile of participants in a study using receipt data from Japan Medical Data Center Co., Ltd. (JMDC): 76.1% were found to be boys [41]. We found the degree of challenging behavior (ABC-I total score) in the children with ASD to be 10.3 ± 8.7.…”
Section: Discussionsupporting
confidence: 87%
“…Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by "de cits in social communication and social interaction" and "restricted, repetitive patterns of behavior, interests, or activities" [1]. In Japan, the prevalence of individuals with ASD is approximately 1% and an upward trend has been reported [2]. Early identi cation and treatment of children with ASD are regarded as important factors for improving their lifetime outcomes [3].…”
Section: Introductionmentioning
confidence: 99%